Further delineation of the clinical spectrum of de novo TRIM8 truncating mutations. Issue 11 (23rd September 2018) - Assoum, Mirna; Lines, Matthew A.; Elpeleg, Orly; Darmency, Véronique; Whiting, Sharon; Edvardson, Simon; Devinsky, Orrin; Heinzen, Erin; Hernan, Rebecca Rose; Antignac, Corinne; Deleuze, Jean‐François; Des Portes, Vincent; et al.
Abstract : De novo mutations of the TRIM8 gene, which codes for a tripartite motif protein, have been identified using whole exome sequencing (WES) in two patients with epileptic encephalopathy (EE), but these reports were not sufficient to conclude that TRIM8 was a novel gene responsible for EE. Here we report four additional patients presenting with EE and de novo truncating mutations of TRIM8 detected by WES, and give further details of the patient previously reported by the Epi4K consortium. Epilepsy of variable severity was diagnosed in children aged 2 months to 3.5 years of age. All patients had developmental delay of variable severity with no or very limited language, often associated with behavioral anomalies and unspecific facial features or MRI brain abnormalities. The phenotypic variability observed in these patients appeared related to the severity of the epilepsy. One patient presented pharmacoresistant EE with regression, recurrent infections and nephrotic syndrome, compatible with the brain and kidney expression of TRIM8. Interestingly, all mutations were located at the highly conserved C‐terminus section of TRIM8. This collaborative study confirms that TRIM8 is a novel gene responsible for EE, possibly associated with nephrotic syndrome. This report brings new evidence on the pathogenicity of TRIM8 mutations and highlights the value of data‐sharing to delineate the phenotypic characteristics and biological basis of extremely rare disorders.